Strength predictions of multi-bolted joints in woven fabric kenaf composite plates with different configurations using xfem frameworks - Khairi, Supar; H., Ahmad (Crimson Publishing, 2018)
Multi-bolted joints are designed as joining technique to provide efficiency in assembling different structure parts; however the ability of neighboring bolts to transfer by-pass stress susceptible to net-tension failure occurrence. More recently, strength prediction works in composite structures are carried out within finite element framework to utilize advantage of advanced computing technology. Current work implemented a three-dimensional Extended Finite Element Method (XFEM) framework of multi-bolted joints configurations in variations lay-ups to determine failure load, validated against experimental datasets. Other testing parameters investigated comprised of different bolts configurations and plate geometries. Visual tracking from XFEM contour found that crack initiation and propagations are consistent with experimental observations. Better agreements were found in nonstaggered configurations with largest discrepancy of approximately 30%, mostly gives less than 15%. Besides, combination of cross-ply and thicker plates promotes better predictions due to larger repetitive plies as current work implemented smeared-out properties within its constitutive model.